Smart learning environment system: e-Commerce module / Saw Yuen Meng @ Chua Yuen Meng - Saw @ Chua Yuen Meng, Yuen Meng (2001)
Smart learning environment system is a system that allows the maintaining and distribution of course materials via the web, administering and grading test for web-based courses, facilitates multilavel threaded discussions among student to student or student to lecture, manages the system and databases for the web-based courses and streamlines the ordering and purchasing of learning materials for web-based courses. This proposal is fully concentrated on building a system for the ordering and purchasing of learning materials for web-based courses. The main objective and significant of the system is to be easily integrated in the smart learning environment system. The learning materials here are computer related books. The system is also known as e-Commmerce Module and is divided into 2 modules, Consumer Module and Admin Module. Consumer Module itself is also divided into 5 more modules there are Order Module, Review Module, Search Module, Register Module and Login Module. While the Admin Module is where all the administartive work is conducted such as deleting, editing and adding new materials into the system. It also consist 4 more modules called Edit Item Module, Edit Review Module, Edit Member Module, Report Module and lastly Category Module. The approached in building the system is based on prototyping and the tools and software that were used to build the system is based on the Open Source concept that is software that are feerly distributed. The software that were used to realized this system are Java, MySQL database, Linux Operating System and Apache Web Server.